Strategies for pneumococcal vaccination in older adults in the coming era - Kei Nakashima; Wakaba Fukushima (Taylor & Francis Group, 2024)
ABSTRACTPneumonia, predominantly caused by Streptococcus pneumoniae, remains a leading cause of global mortality. The 23-valent Pneumococcal polysaccharide vaccine (PPSV23) and conjugate vaccines (PCVs) are vital measures to fight against it. This paper discussed the changes in pneumococcal vaccination strategies, particularly for older adults, as vaccine effectiveness and epidemiological patterns shift. While PPSV23 maintains effectiveness against invasive pneumococcal disease (IPD), its effectiveness against pneumococcal pneumonia is declining. Conversely, PCV13 consistently demonstrates effectiveness against both IPD and pneumonia. Consequently, the US Centers for Disease Control and Prevention's Advisory Committee on Immunization Practices recommends using PCVs, notably PCV20 and PCV15, over PPSV23. Japanese studies indicate a change in the efficacy/effectiveness of PPSV23 following PCV introduction in children, likely owing to serotype replacement and herd immunity. Additionally, recent data reveals a plateau in the reduction of PCV13 and PPSV23-covered serotypes, posing a challenge to current strategies. This paper indicates a paradigm shift in pneumonia management, acknowledging its chronic nature and potential to exacerbate other diseases. The future of pneumococcal vaccination lies in broader serotype coverage through PCVs, adapting to serotype changes driven by childhood vaccination programs. Furthermore, continuous research and vaccine development are crucial in this evolving field.